2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487216
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic isotropy in 3-DOF Gantry Tau robots - an analytical study

Abstract: 3-DOF Gantry Tau is a type of parallel robot, consisting of six struts configured in three clusters, which provides three translational DOFs. It has increasing industrial use in applications where large workspace and high stiffness are required. In fact, the concept of dynamic isotropy, where all the natural frequencies of a system are equal, can be employed in order to effectively optimize the geometry of robots. However, no study on dynamic isotropy of Gantry Tau robots has yet been reported in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The authors have compared the AKP approach with PD and non-linear PD approach and concluded that it's more promising. Afzali-Far et al [18] have addressed the problem of design of a 3-DOF Gantry Tau robot using the concept of dynamic isotropy for the first time. This concept can be used to optimize the geometry of robots.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have compared the AKP approach with PD and non-linear PD approach and concluded that it's more promising. Afzali-Far et al [18] have addressed the problem of design of a 3-DOF Gantry Tau robot using the concept of dynamic isotropy for the first time. This concept can be used to optimize the geometry of robots.…”
Section: Introductionmentioning
confidence: 99%